2010
DOI: 10.1007/s11104-010-0608-7
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of mineralization to grassland N uptake on peatland soils with anthropogenic A horizons

Abstract: Peatland soils contain large amounts of nitrogen (N) in the soil and mineralization can contribute substantially to the annual mineral N supply of grasslands. We investigated the contribution of N mineralization from peat with respect to the total annual N uptake on grasslands with anthropogenic A horizons and submerged tile drains. The study included i) a pot experiment to determine potential N mineralization from the topsoil and the subsoil, ii) a 1-year field experiment to study herbage yields and N uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…These observations concur with those of Magdoff (1978) who concluded that soils with high soil N mineralization rates do mineralize N from added manure more rapidly compared to soils with lower inherit N availability rates. It should be noted that in our experiment the TNR values and net N mineralization potential of the peat soil could have been stimulated by the long-term (>50 years) high input rates of crop residues, ditch sludge and animal manures on the dairy farm where this soil was collected (Sonneveld and Lantinga 2010). This farming practice has led to a build-up of young soil OM including young organic N Fig.…”
Section: Discussionmentioning
confidence: 72%
“…These observations concur with those of Magdoff (1978) who concluded that soils with high soil N mineralization rates do mineralize N from added manure more rapidly compared to soils with lower inherit N availability rates. It should be noted that in our experiment the TNR values and net N mineralization potential of the peat soil could have been stimulated by the long-term (>50 years) high input rates of crop residues, ditch sludge and animal manures on the dairy farm where this soil was collected (Sonneveld and Lantinga 2010). This farming practice has led to a build-up of young soil OM including young organic N Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The observed quadratic increase of plantain N yields at higher plantain DM yields partly confirmed our hypothesis that the presence of plantain can increase the N use efficiency of grassland on peat soil since on the other hand no effects of the presence and yield of plantain on ryegrass N yields were observed (Figure 2). In our experiment plant N contents were low (1.94 ± 0.32 g kg −1 DM) compared to field conditions (typically summer and autumn N contents without fertilisation are ≥2.40 g kg −1 DM) (Vellinga and Andre 1999;Sonneveld and Lantinga 2011;Deru et al 2019). Soil mineral N, P AL , K and pH conditions were not likely to have limited plant N uptake (CBGV 2017).…”
Section: Mesocosm Experimentsmentioning
confidence: 63%
“…It is well known that drainage enhances the degradation of soil organic matter (SOM) and thus stimulates net nitrogen mineralization and N transformation processes (Kasimir Klemedtsson et al, 1997;Freibauer et al, 2004;Klemedtsson et al, 2005;Goldberg et al, 2010). Various studies reported an annual N supply through peat mineralization of 70 to 292 kg N ha −1 yr −1 (Schothorst, 1977;Flessa et al, 1998;Sonneveld and Lantinga, 2011). It can be assumed that at a comparable aeration status and temperature, mineralization processes are more intensive at peatlands that were recently drained (Hacin et al, 2001;Renger et al, 2002;Sonneveld and Lantinga, 2011) or contain higher amounts of SOM.…”
Section: Drainage and Fertilizer Effects On N-availability And N-tranmentioning
confidence: 99%
“…Various studies reported an annual N supply through peat mineralization of 70 to 292 kg N ha −1 yr −1 (Schothorst, 1977;Flessa et al, 1998;Sonneveld and Lantinga, 2011). It can be assumed that at a comparable aeration status and temperature, mineralization processes are more intensive at peatlands that were recently drained (Hacin et al, 2001;Renger et al, 2002;Sonneveld and Lantinga, 2011) or contain higher amounts of SOM. As expected from the literature, the biogas digestates differed in their physical and chemical properties from the cattle slurries.…”
Section: Drainage and Fertilizer Effects On N-availability And N-tranmentioning
confidence: 99%